Snitching : Criminal Informants and the Erosion of American Justice. - Natapoff, Alexandra (NYU Press, 2009)
Winner of the 2010 American Bar Association Honorable Mention for Books. Albert Burrell spent thirteen years on death row for a murder he did not commit. Atlanta police killed 92-year-old Kathryn Johnston during a misguided raid on her home. After being released by Chicago prosecutors, Darryl Moore--drug dealer, hit man, and rapist--returned home to rape an eleven-year-old girl. Such tragedies are consequences of snitching--police and prosecutors offering deals to criminal offenders in exchange for information. Although it is nearly invisible to the public, criminal snitching has invaded the Amer.